Method for manufacturing resin sheets

JP2026165501APending Publication Date: 2026-10-14SUMITOMO BAKELITE CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025057917
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

Smart Images

  • Figure 2026165501000001_ABST
    Figure 2026165501000001_ABST
Patent Text Reader

Abstract

This invention provides a method for manufacturing a resin sheet having a curved surface nanostructure. [Solution] The method for manufacturing the resin sheet 100 includes the steps of: step 1, overlapping a flat sheet 110 having a nanostructure 10 on one surface with the side of the nanostructure 10 facing a perforated plate 30; and step 2, pressing the flat sheet 110 into the holes 31 of the perforated plate 30 to form a convex surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a resin sheet.

Background Art

[0002] Conventionally, it is known to impart various properties by subjecting a resin sheet to three-dimensional processing. For example, as a method for curving a resin sheet, as disclosed in Patent Document 1 (Japanese Unexamined Patent Application Publication No. 2023-171753), a method is known in which an optical film is vacuum-suctioned through a porous mold having a desired curved surface to conform the optical film to the curved surface.

Prior Art Documents

Patent Documents

[0003]

Patent Document 1

Summary of Invention

Problems to be Solved by the Invention

[0004] The present inventors focused on the development of a resin sheet having a newly curved surface nanostructure, and found that when a resin sheet having a surface nanostructure is curved by a method as disclosed in Patent Document 1, a load is applied to the surface nanostructure by press pressure and vacuum suction, which may cause problems such as deformation of the surface nanostructure. Accordingly, an object of the present invention is to realize a production method capable of suitably maintaining the surface nanostructure even when a resin sheet having the surface nanostructure is subjected to curving processing.

Means for Solving the Problems

[0005] The present inventors newly focused on using a perforated plate as a method for curving a resin sheet having a surface nanostructure, and completed the present invention.

[0006] [1] A method for manufacturing a resin sheet having a curved portion having a nanostructure on its convex surface, A step of stacking a flat sheet having a nanostructure on one of its surfaces with the nanostructure side facing a perforated plate, The steps include pressing the flat sheet into the holes of the perforated plate to form the convex surface, A method for manufacturing a resin sheet having the following characteristics. [2] A method for manufacturing a resin sheet as described in [1], Before the step of forming the convex surface, A method for manufacturing a resin sheet, comprising the step of heating the flat sheet. [3] [2] A method for manufacturing a resin sheet, The step of heating the flat sheet is to heat it to 150-180°C, in a method for manufacturing a resin sheet. A method for manufacturing a resin sheet as described in any one of [4] [1] to [3], The step of forming the convex surface is a method for manufacturing a resin sheet, in which the flat sheet is pressed into each hole of the perforated plate. A method for manufacturing a resin sheet as described in any one of [1] to [4], A method for manufacturing a resin sheet, further comprising the step of cutting the flat sheet to obtain a resin sheet after the step of forming the convex surface. A method for manufacturing a resin sheet as described in any one of [6] [1] to [5], A method for manufacturing a resin sheet, wherein the flat sheet is in the form of a single leaf or a continuous roll. A method for manufacturing a resin sheet as described in any one of [7] [1] to [6], A method for manufacturing a resin sheet, wherein the radius of curvature of the convex surface is 10 to 500 mm. A method for manufacturing a resin sheet as described in any one of [8] [1] to [7], The resin sheet is a resin sheet containing polycarbonate, and the method for manufacturing a resin sheet. A method for manufacturing a resin sheet as described in any one of [9] [1] to [8], The method for manufacturing a resin sheet, wherein the nanostructure is a fine uneven structure with an average pitch of 20 nm to 1000 nm. A method for manufacturing a resin sheet as described in any one of [1] to [9], A method for manufacturing a resin sheet, wherein the thickness of the resin sheet is 0.1 to 0.8 mm. A method for manufacturing a resin sheet as described in any one of [1] to

[10] , The resin sheet in question is used in optical components, and the method for manufacturing a resin sheet. [Effects of the Invention]

[0007] According to the present invention, a method for manufacturing a resin sheet having a curved surface nanostructure can be provided. [Brief explanation of the drawing]

[0008] [Figure 1] This figure schematically shows a cross-section of the resin sheet of this embodiment. [Figure 2] This is an enlarged view showing a cross-section of the nanostructure of the resin sheet of this embodiment. [Figure 3] This is a schematic diagram illustrating the manufacturing method of the resin sheet according to this embodiment. [Figure 4] This is a schematic diagram illustrating the manufacturing method of the resin sheet according to this embodiment. [Modes for carrying out the invention]

[0009] Embodiments of the present invention will be described in detail below with reference to the drawings. To avoid complexity, if multiple identical components appear in the same drawing, only one may be assigned a reference numeral, and none of them may be assigned a reference numeral. All drawings are for illustrative purposes only. The shapes and dimensional ratios of each component in the drawings do not necessarily correspond to actual items.

[0010] In the present specification, the notation "a to b" in the description of numerical ranges means a value equal to or greater than a and equal to or less than b, unless otherwise specified. For example, "1 to 5 mass%" means "1 mass% or more and 5 mass% or less". In addition, the lower limit and upper limit of a numerical range can be arbitrarily combined with the lower limit and upper limit of any other numerical range, respectively.

[0011] Unless otherwise specified, each component and material exemplified in the present specification may be used alone, or two or more thereof may be used in combination.

[0012] <Resin Sheet> Figure 1 is a diagram schematically showing the cross section of the resin sheet of the present embodiment, and Figure 2 is an enlarged view showing the cross section of the nanostructure of the resin sheet of the present embodiment. As shown in Figures 1 and 2, the resin sheet 100 of the present embodiment includes a curved portion 11 having a nanostructure 10 on its convex surface, and comprises a surface layer 21 having the nanostructure 10, and a base material layer 22 provided on the surface of the surface layer 21 opposite to the side having the nanostructure 10.

[0013] Since the resin sheet 100 of the present embodiment has the nanostructure 10 on its convex surface, it has properties such as water repellency and anti-light reflection properties, and further, by being provided with the curved portion 11, it can be used in various fields such as lenses. Details will be described later.

[0014] <Method for Manufacturing Resin Sheet> Next, an example of the method for manufacturing the resin sheet 100 will be described using Figures 3 and 4. The method for manufacturing the resin sheet 100 of the present embodiment includes a step (step 1) of stacking a flat sheet 110 having the nanostructure 10 on one surface such that the surface on the nanostructure 10 side faces the perforated plate 30, and a step (step 2) of pressing the flat sheet 110 into the hole portion 31 of the perforated plate 30 to form a convex surface. Hereinafter, details of each step will be described.

[0015] [Step 1] First, a flat sheet 110 having a nanostructure 10 on one surface is prepared. The flat sheet 110 is the sheet before the curved portion 11 of the resin sheet 100 is formed. The method for creating the flat sheet 110 having the nanostructure 10 is not particularly limited, and known methods can be used. For example, the flat sheet 110 having the nanostructure 10 can be created as follows.

[0016] A UV-curable resin composition is coated onto one surface of the base layer 22, and then a mold with fine irregularities is pressed onto the coating film to transfer the irregular shape. Subsequently, UV light is irradiated onto the film-like UV-curable resin from the base layer 22 side to cure the UV-curable resin composition and form a surface layer 21 (flat sheet 110) having a nanostructure 10 on its surface. The base layer 22 is obtained by this curing process.

[0017] The mold having the fine irregularities is not particularly limited, but for example, a glassy carbon layer can be used. Details of the glassy carbon layer will be described later in the method for forming the surface layer 21.

[0018] Next, the side of the flat sheet 110 having the nanostructure 10 facing the perforated plate 30 is placed opposite each other and superimposed (Figure 3). The region facing the holes 31 of the perforated plate 30 will later become the curved portion 11.

[0019] The perforated plate 30 is used to give a curved portion 11 to the flat sheet 110, and the plate can have holes (opening diameters) of a size appropriate to the size, purpose, and application of the curved portion 11, as well as a thickness appropriate to the purpose. For example, the opening diameter of the hole 31 may be 10 to 100 mm. In this case, by making the opening diameter of the hole 31 less than the circumference of the pressing portion of the pressing tool 40 described later, distortion can be reduced and a spherical shape can be formed.

[0020] Furthermore, the plate thickness may be 10 to 50 mm. By setting the plate thickness to be greater than or equal to the lower limit mentioned above, when forming the protrusions in step 2 described later, the open state of the upper surface of the protrusions can be maintained, and it is possible to suppress the nanostructure 10 from coming into contact with a jig or the like and deforming.

[0021] Furthermore, the material of the perforated plate 30 is not particularly limited, but may be metal, resin, wood, etc. Among these, metal is preferred.

[0022] The flat sheet 110 may be in the form of a single sheet or a continuous roll, but it may be cut before step 2 described later, according to the size of the holes 31 in the perforated plate 30. This makes it easier for a portion of the flat sheet 110 to slide into the holes 31 in step 2, thereby reducing deformation of the nanostructure 10. In other words, it is preferable that the size of the flat sheet 110 be large enough to cover the holes 31 in the perforated plate 30, and also large enough to continue covering the holes 31 even if a portion of the flat sheet 110 slides into the holes 31 due to the bending process in step 2 described later.

[0023] [Process 2] Next, the flat sheet 110 is pressed into the hole 31 of the perforated plate 30 to form a convex surface. That is, the flat sheet 110 is pressed from the surface of the flat sheet 110 facing the hole 31 of the perforated plate 30, and the flat sheet 110 is pushed into the hole 31 (Figure 4(a)). In this case, it is preferable that the flat sheet 110 is not fixed, but rather a part of the flat sheet 110 slides into the hole 31 as it is pressed in. This suppresses the load on the nanostructure 10 on the surface of the flat sheet 110 and reduces deformation of the nanostructure 10. As a result, the occurrence of cracks and wrinkles is suppressed, and good transparency and water repellency are maintained.

[0024] Furthermore, it is preferable to heat the flat sheet 110 before pressing it into the holes 31 of the perforated plate 30. This makes the flat sheet 110 more flexible, making it easier to bend and further reducing the load on the nanostructure 10. The heating temperature is preferably 150 to 180°C. The heating time is preferably 5 to 15 minutes. Alternatively, the perforated plate 30 may be preheated, or the flat sheet 110 may be placed on the perforated plate 30 and heated, or both may be done.

[0025] When pressing, a pressing tool 40 may be used that is appropriate to the shape of the curved portion 11 and the size of the hole 31. The pressing tool 40 has a curved tip and is used by inserting it into the hole 31 from the surface of the flat sheet 110 that is on the base material layer 22 side, thereby forming the curved portion 11 in the flat sheet 110. The pressing strength is adjusted as appropriate according to the application and purpose.

[0026] Specifically, for example, the tip of the pressing tool 40 may be a hemispherical portion with a diameter larger than the diameter of the hole 31 of the perforated plate 30, and this hemispherical portion may be pressed against the flat sheet 110 and pressed into the hole 31. In this case, by pressing until the outer edge of the hemispherical portion of the pressing tool 40 touches the edge of the hole 31, a convex surface of the same shape can be stably manufactured.

[0027] The resin sheet 100 can be obtained by following the procedure described above (Figure 4(b)). The resin sheet 100 may be further processed depending on the purpose and application.

[0028] The details of the resin sheet 100 are described below.

[0029] (curvature radius) In the embodiment, the resin sheet 100 preferably has a convex radius of curvature of 10 to 500 mm, more preferably 10 to 250 mm, and even more preferably 10 to 150 mm. By setting the radius of curvature of the convex surface to be greater than or equal to the lower limit mentioned above, good water repellency can be obtained while retaining the functionality provided by the convex surface. On the other hand, by setting the radius of curvature of the convex surface to below the above upper limit, deformation of the nanostructure 10 is suppressed, making it easier to maintain good water repellency.

[0030] The radius of curvature of a convex surface can be calculated by spraying, for example, Helling 3-D Anti Glare Spray from Helling Corporation onto a resin sheet 100, and then measuring the 3D shape using a Keyence VR-5000.

[0031] (Thickness) The thickness of the resin sheet 100 is preferably 0.1 mm or more, more preferably 0.2 mm or more, and even more preferably 0.3 mm or more. By setting the thickness of the resin sheet 100 to be above the above lower limit, it is possible to suppress the warping of the sheet that occurs during thermoforming. The thickness of the resin sheet 100 is preferably 1.5 mm or less, more preferably 0.8 mm or less, and even more preferably 0.5 mm or less. By making the thickness of the resin sheet 100 below the above upper limit, the operability during molding can be improved.

[0032] (Light transmittance) The light transmittance of the resin sheet 100 at a wavelength of 550 nm is preferably 90-95%, more preferably 91-95%, and even more preferably 92-95%. The light transmittance is preferable as long as it is high, from the standpoint of achieving transparency.

[0033] The light transmittance of resin sheet 100 can be measured using a spectrophotometer (V-670, manufactured by [Company Name]).

[0034] The following describes the surface layer 21 having the nanostructure 10 of the resin sheet 100 and the base layer 22 provided on the side of the surface layer 21 opposite to the nanostructure 10.

[0035] [Surface layer 21] The surface layer 21 forms one outer surface of the resin sheet 100 and has the nanostructure 10 on the side that forms the outer surface. The surface layer 21 also has a curved portion 11, and the nanostructure 10 is on the convex side of the curved portion 11.

[0036] The thickness (T1) of the surface layer 21 is preferably 3 μm or more, more preferably 5 μm or more, and even more preferably 10 μm or more. By setting the thickness (T1) of the surface layer 21 to be above the lower limit, sufficient weather resistance can be provided. The thickness (T1) of the surface layer 21 is preferably 30 μm or less, more preferably 25 μm or less, and even more preferably 20 μm or less. By setting the thickness (T1) of the surface layer 21 to be below the above upper limit, it is possible to form a spherical shape without cracks forming in the surface layer 21. Note that the thickness of the surface layer 21 (T1) includes the height of the vertices of the nanostructure 10.

[0037] Furthermore, when the thickness of the surface layer 21 is T1 (μm) and the thickness of the base layer 22 described later is T2 (μm), T1 / T2 is preferably 0.006 to 0.3, more preferably 0.010 to 0.1, and even more preferably 0.015 to 0.05.

[0038] The refractive index of the surface layer 21 at a wavelength of 589 nm is not particularly limited, but is preferably 1.40 or more and 1.60 or less, and more preferably 1.450 or more and 1.595 or less.

[0039] (Nanostructure) The nanostructure 10 is preferably a fine uneven structure with an average pitch of 20 nm to 1000 nm. More preferably, the average pitch is 30 nm to 800 nm, even more preferably 40 nm to 600 nm, and even more preferably 50 nm to 500 nm. By setting the average pitch above the lower limit, the release properties in the nanoimprint process are improved. On the other hand, by setting the average pitch below the upper limit, the resistance to wiping and the ability to slide off fine water droplets can be improved. The average pitch can be defined as the average interval between convexities.

[0040] The average height of the protrusions in the nanostructure 10 is preferably 10 nm to 1600 nm, more preferably 30 nm to 1000 nm, and even more preferably 100 nm to 500 nm.

[0041] Furthermore, when the protrusions in the nanostructure 10 are cylindrical or needle-shaped, the average diameter at the base end of the protrusions is 5 nm or more and 600 nm or less, more preferably 10 nm or more and 400 nm or less, and even more preferably 50 nm or more and 150 nm or less.

[0042] The average pitch and average height of the protrusions of the nanostructure 10 can be measured by observing the cross-section using a scanning electron microscope (SEM).

[0043] The surface layer 21 may be formed using an ultraviolet-curable resin composition, or a commercially available resin film having a nanostructure may be used. When using an ultraviolet-curable resin composition, it is specifically obtained by pressing a mold having a desired surface shape against the ultraviolet-curable resin composition and curing it. Below, a method for forming the surface layer 21 using a glassy carbon layer as the mold will be described.

[0044] [Method for forming the surface layer] First, glassy carbon is laminated onto a substrate by sputtering or the like to form a glassy carbon layer. The glassy carbon layer 52 preferably has an average thickness of 300 nm to 5 μm, and more preferably 500 nm to 3 μm.

[0045] Glassy carbon, also known as glassy carbon or amorphous carbon, has a homogeneous and dense structure. When performing a glassy carbon layer deposition process using a DC power supply sputtering method, by setting appropriate conditions for sputtering power, deposition pressure, etc., it is possible to deposit a glassy carbon layer with small grain boundaries and high film density. Specifically, the sputtering power should be 0.5 kW or more and 5 kW or less, preferably 1.0 kW or more and 3.0 kW or less, more preferably 1.0 kW or more and 2.0 kW or less, and the deposition pressure should be 1.0 Pa or less, preferably 8 × 10⁻⁶. -1 Pa or less, more comfortable 5 x 10 -1 It's best to use Pa.

[0046] The base material is not particularly limited, and known materials may be used, but examples include metals, alloys, ceramics (metal oxides, metal nitrides, metal oxynitrides), silicon (Si), etc., and one or more of these can be used in combination.

[0047] Next, the glassy carbon layer laminated on the substrate is etched with an oxygen ion beam or oxygen plasma. A reaction gas may be used during this process. As the reaction gas, an oxygen-containing gas may be used; oxygen alone may be used, or a gas mixed with oxygen and a CF-based gas such as CF4 may be used. In addition, a noble gas such as argon may be mixed in to change the ion current density and plasma density. Etching can create fine recesses on the surface of the glassy carbon layer. Furthermore, by controlling the etching acceleration voltage, gas flow rate, and processing time, the shape (size, width, angle, etc.) and pitch of the fine recesses can be controlled.

[0048] The glassy carbon layer obtained in this way is used as a mold, and the side with the glassy carbon layer is pressed against the UV-curable resin composition to transfer the surface shape. While transferring, 405 nm UV light at 1500 mJ / cm² is applied. 2 The surface layer 21 is obtained by curing the resin material by irradiating it under these conditions.

[0049] The following describes UV-curable resin compositions.

[0050] [Ultraviolet curable resin composition] The UV-curable resin composition preferably contains a polymerizable component, a polymerization initiator, and a UV absorber.

[0051] (Polymerizable components) The polymerizable component has polymerizable groups. The reaction of these polymerizable groups forms a network (polymer chain), resulting in a cured product of the UV-curable resin composition.

[0052] In the polymerizable component, examples of polymerizable groups include radical polymerizable groups and cationic polymerizable groups, but radical polymerizable groups are preferred.

[0053] The polymerizable component may be a monomer, oligomer, or polymer, as long as it has polymerizable groups, but it is preferably a monomer or oligomer. This makes it possible to lower the viscosity of the UV-curable resin composition, making it easier to form a uniform film when it is applied. As a result, the film thickness of the surface layer 21 made of the UV-curable resin composition can be made uniform. Furthermore, when a mold for forming the nanostructure 10 is pressed against the surface of the film using the UV-curable resin composition to transfer the irregularities, the mold follows the irregularities well, improving the transferability.

[0054] Furthermore, if an ultraviolet-curable resin composition contains both a polymerizable component with radical polymerizable groups and a polymerizable component with cationic polymerizable groups, and their curing is started almost simultaneously, the formation of the cured product by the polymerizable component with radical polymerizable groups is faster. In other words, radical polymerizable groups have a faster reaction rate than cationic polymerizable groups, and are therefore preferred for use.

[0055] The following explanation will use the case where the polymerizable component is a monomer or oligomer component that possesses a radical polymerizable group as an example.

[0056] Examples of radical polymerizable groups include (meth)acryloyl groups and vinyl groups, but (meth)acryloyl groups are preferred. (Meth)acryloyl groups are preferred as radical polymerizable groups because they exhibit excellent radical polymerizability and because compounds containing (meth)acryloyl groups as polymerizable groups are readily available. In other words, so-called acrylic monomers are preferred as monomer components.

[0057] Furthermore, in an ultraviolet-curable resin composition, in order to form a network based on the reaction between polymerizable components, it is preferable that the polymerizable components have multiple (two or more) radical polymerizable groups, and it is more preferable that both components having two radical polymerizable groups and components having three or more radical polymerizable groups are included. This allows for the formation of a stronger network in the cured product of the ultraviolet-curable resin composition.

[0058] Furthermore, in polymerizable components, when the region incorporated into the network by linking radical polymerizable groups is considered the main chain of the polymerizable component, examples of this main chain include linear or branched chains having urethane bonds, linear or branched chains having ester bonds, linear or branched chains having epoxy bonds, linear or branched chains of glycols, and linear or branched chains having repeating siloxane bonds (-Si-O-Si-). Among these, those exhibiting relatively good flexibility, such as linear or branched chains having urethane bonds, linear or branched chains having ester bonds, linear or branched chains having epoxy bonds, and linear or branched chains of glycols, are preferably selected. Specifically, for example, a linear chain having a urethane bond (-OCONH-) is linked to a (meth)acryloyl group as a side chain, i.e., urethane (meth)acrylate. This urethane acrylate may be either a monomer or an oligomer. This ensures that the cured product of the UV-curable resin composition is reliably soft. Therefore, the conformability of the film composed of the UV-curable resin composition to the mold is improved, and as a result, even nanostructures 10 with finer shapes can be formed with excellent precision on the surface of the surface layer 21.

[0059] Based on the above, it is preferable that the polymerizable component consists of a straight or branched glycol chain as the main chain, to which a (meth)acryloyl group as a radical polymerizable group is linked. When the polymerizable component has two radical polymerizable groups, a straight glycol chain is selected as the main chain, and when it has three or more radical polymerizable groups, a branched glycol chain is selected as the main chain.

[0060] Furthermore, in this case, the main chain (straight or branched) of the glycol preferably contains an aliphatic chain having 3 to 10 carbon atoms. That is, the polymerization component preferably has a radical polymerizable group and an aliphatic chain having 3 to 10 carbon atoms within its backbone. This makes it possible to more reliably obtain a soft (flexible) cured product of the UV-curable resin composition.

[0061] Furthermore, in polymerizable components, when regions that are not incorporated into the network due to linkage between radical polymerizable groups are considered as side chains of the polymerizable components, it is preferable that the polymerizable components, in addition to those described above, also contain fluorinated hydrocarbon groups as side chains. That is, it is preferable that the polymerizable components have radical polymerizable groups and fluorinated hydrocarbon groups within their skeleton. As a result, when the polymerizable components (monomer components and oligomers) polymerize and a cured product of the UV-curable resin composition is formed, the UV-curable resin composition hardens with a configuration in which fluorinated hydrocarbon groups are exposed on the surface of the cured product. Therefore, the surface of the cured product of the UV-curable resin composition, i.e., the surface of the surface layer 21 on which the nanostructure 10 is formed, has a configuration in which these fluorinated hydrocarbon groups as side chains are exposed. Thus, excellent water repellency can be imparted to the surface of the surface layer 21. In addition, the exposure of fluorinated hydrocarbon groups on the surface layer 21 allows the surface layer 21 to exhibit excellent sliding properties.

[0062] Furthermore, the content of polymerizable components in the UV-curable resin composition is not particularly limited, but it is preferably 40 parts by mass or more and 95 parts by mass or less per 100 parts by mass of the UV-curable resin composition, and more preferably 70 parts by mass or more and 95 parts by mass or less. By setting the content of polymerizable components in the UV-curable resin composition within the aforementioned range, the surface layer 21 can be provided such that the nanostructure 10 is formed on its surface with excellent precision.

[0063] Furthermore, if the polymerizable component contains a polymerizable component having a fluorinated hydrocarbon group as a side chain, the content of this polymerizable component is preferably 0.1 parts by mass or more and 5.0 parts by mass or less, and more preferably 0.3 parts by mass or more and 2.5 parts by mass or less, per 100 parts by mass of the UV-curable resin composition. This ensures that the UV-curable resin composition reliably exhibits the effects obtained by containing a polymerizable component having a fluorinated hydrocarbon group as a side chain.

[0064] (Polymerization initiator) Furthermore, the UV-curable resin composition contains a polymerization initiator to initiate a polymerization reaction that forms a network of polymerization components. As mentioned above, when the polymerizable component has a radical polymerizable group as a polymerizable group, it is preferable to include a radical polymerization initiator (photoradical polymerization initiator) that generates radicals when irradiated with ultraviolet light as an energy ray, as the polymerization initiator.

[0065] This allows for the reliable generation of radicals from the photoradical polymerization initiator by irradiating the film composed of the UV-curable resin composition with ultraviolet light while pressing a mold against its surface. Consequently, these radicals can initiate a polymerization reaction by polymerizable components that possess radical polymerizable groups as polymerizable groups. Therefore, a surface layer 21 on which the nanostructure 10 is formed can be stably created.

[0066] Furthermore, while there are no particular limitations on the photoradical polymerization initiator, examples include acetophenone-based photoradical polymerization initiators, benzoin-based photoradical polymerization initiators, thioxanthone-based photoradical polymerization initiators, ketone-based photoradical polymerization initiators, imidazole-based photoradical polymerization initiators, carbazole-based photoradical polymerization initiators, oxime ester-based photoradical polymerization initiators, titanocene-based photoradical polymerization initiators, acylphosphine oxide-based photoradical polymerization initiators, trichloromethyltriazine-based photoradical polymerization initiators, and one or more of these can be used in combination.

[0067] Furthermore, it is preferable that this photoradical polymerization initiator has a photoabsorption peak in its photoabsorption spectrum that has a maximum absorption peak in the wavelength range of over 350 nm and up to 400 nm.

[0068] Here, the UV absorber described later is generally one that has a light absorption peak with a maximum absorption rate in the wavelength range of 300 nm to 350 nm in its light absorption spectrum, with the aim of suppressing the alteration and deterioration of the resin sheet 100 of the surface layer 21 due to exposure to sunlight. Therefore, even if UV light in the wavelength range of 300 nm to 350 nm is absorbed by the UV absorber when UV light is irradiated using the UV irradiation means 830, the photoradical polymerization initiator has a maximum absorption rate peak in the wavelength range of over 350 nm and up to 400 nm, so it can reliably generate radicals by absorbing UV light in this range.

[0069] The content of the photoradical polymerization initiator in the UV-curable resin composition is not particularly limited, but is preferably 1.0 part by mass or more and 8.0 parts by mass or less, and more preferably 3.0 parts by mass or more and 6.5 parts by mass or less, per 100 parts by mass of the UV-curable resin composition. By setting the content of the photoradical polymerization initiator within the above range, radicals can be reliably generated by the absorption of ultraviolet light by the photoradical polymerization initiator.

[0070] (UV absorber) The UV-curable resin composition contains a UV absorber, which allows it to absorb ultraviolet light within the surface layer 21. Therefore, it is possible to suppress the alteration and degradation of other constituent materials contained in the UV-curable resin composition.

[0071] While not particularly limited, examples of UV absorbers include triazine-based, benzophenone-based, benzotriazole-based, and cyanoacrylate-based types, and one or two of these can be used in combination. Among these, benzotriazole-based UV absorbers are particularly preferred, and among benzotriazole-based UV absorbers, hydroxyphenylbenzotriazole-based UV absorbers are more preferred.

[0072] Furthermore, it is preferable that the UV absorber has a functional group that is reactive with the polymerization component. Specifically, if the polymerizable component is a monomer component having a radical polymerizable group, it is preferable that the UV absorber has a radical polymerizable group as a functional group. This allows the UV absorber to be incorporated into the network formed by the reaction of the polymerization component. Therefore, it is possible to effectively suppress the leakage, or bleed-out, of the UV absorber from the surface layer 21 composed of the cured product of the UV-curable resin composition.

[0073] Furthermore, when the polymerizable group of the polymerization component is a (meth)acryloyl group, an ultraviolet absorber having a (meth)acryloyl group as a functional group that reacts with the polymerization component (radical polymerization component) is preferably used as an ultraviolet absorber having a functional group that reacts with the radical polymerization component because the (meth)acryloyl groups of both the polymerization component and the (meth)acryloyl groups can form a network through radical polymerization. In addition, an ultraviolet absorber having a (meth)acryloyl group as a functional group can be obtained, for example, as a reaction product of a hydroxyphenylbenzotriazole ultraviolet absorber having two or more hydroxyl groups and a (meth)acrylate monomer. In hydroxyphenylbenzotriazole ultraviolet absorbers, one hydroxyl group adjacent to the triazine skeleton is present in order to exhibit the function of an ultraviolet absorber. Therefore, in order to impart reactivity with the (meth)acrylate monomer to a hydroxyphenylbenzotriazole ultraviolet absorber, the hydroxyphenylbenzotriazole ultraviolet absorber (benzotriazole ultraviolet absorber) is required to have one or more hydroxyl groups different from this hydroxyl group.

[0074] Furthermore, the content of the ultraviolet absorber in the ultraviolet-curable resin composition is not particularly limited, but it is preferably 2.0 parts by mass or more and 5.0 parts by mass or less per 100 parts by mass of the ultraviolet-curable resin composition, and more preferably 2.5 parts by mass or more and 4.5 parts by mass or less. If the content of the ultraviolet absorber in the ultraviolet-curable resin composition is below the lower limit, depending on the type of ultraviolet absorber, the effect obtained by adding the ultraviolet absorber to the surface layer 21 may not be sufficiently obtained. Also, even if the content of the ultraviolet absorber in the ultraviolet-curable resin composition exceeds the upper limit, no further improvement in ultraviolet irradiation resistance will be observed, and there is a risk of reducing the transparency of the surface layer 21 and the adhesion of the surface layer 21 to the substrate layer 22.

[0075] The UV-curable resin composition may further contain other additives besides the materials described above.

[0076] Other additives include, for example, light stabilizers, heat absorbers, plasticizers, colorants, sensitizers, surfactants, antioxidants, reduction inhibitors, antistatic agents, and surface modifiers (leveling agents).

[0077] The UV-curable resin composition having such a configuration may further contain a solvent as another additive, but it is preferable that it is a solvent-free resin composition that is substantially free of solvents. This makes it possible to form a surface layer 21 by curing the UV-curable resin composition by irradiating it with ultraviolet light through a transparent substrate layer 22 while pressing a mold against the surface of the film made of the UV-curable resin composition, with better film formation accuracy.

[0078] Furthermore, when the UV-curable resin composition is a solvent-free resin composition, monomer components are preferably selected as polymerizable components, as described above. This allows for the preparation of a UV-curable resin composition with low viscosity, specifically, a viscosity of approximately 30 cP to 200 cP, more preferably 50 cP to 120 cP, even when the UV-curable resin composition is a solvent-free resin composition.

[0079] [Base material layer 22] The base layer 22 serves as the base material for the resin sheet 100, and is preferably composed mainly of a polycarbonate resin.

[0080] Furthermore, "main material" refers to the constituent material that makes up 50% by weight or more of the constituent materials of the layer (base material) containing this material.

[0081] Polycarbonate resins are rich in transparency (light transmission) and mechanical strength such as rigidity, and also have high heat resistance. Therefore, by selecting a polycarbonate resin as the transparent resin, the transparency of the base layer 22, as well as the impact resistance and heat resistance of the base layer 22, can be improved.

[0082] Various types of polycarbonate resins can be used, but aromatic polycarbonate resins are preferred. Aromatic polycarbonate resins have aromatic rings in their main chain, which allows for the creation of a base layer 22 with superior strength.

[0083] Aromatic polycarbonate resins are synthesized, for example, by interfacial polycondensation reactions between bisphenol and phosgene, or by transesterification reactions between bisphenol and diphenyl carbonate.

[0084] Examples of bisphenols include bisphenol A and bisphenol (modified bisphenol) which is the origin of the repeating units of polycarbonate shown in formula (1A) below.

[0085] [ka] (In formula (1A), X is an alkyl group, aromatic group, or cyclic aliphatic group having 1 to 18 carbon atoms; Ra and Rb are each independently an alkyl group having 1 to 12 carbon atoms; m and n are each integers from 0 to 4; and p is the number of repeating units.)

[0086] Specifically, examples of bisphenols that originate from the repeating units of the polycarbonate shown in formula (1A) include 4,4'-(pentane-2,2-diyl)diphenol, 4,4'-(pentane-3,3-diyl)diphenol, 4,4'-(butane-2,2-diyl)diphenol, 1,1'-(cyclohexanediyl)diphenol, 2-cyclohexyl-1,4-bis(4-hydroxyphenyl)benzene, 2,3-biscyclohexyl-1,4-bis(4-hydroxyphenyl)benzene, 1,1'-bis(4-hydroxy-3-methylphenyl)cyclohexane, 2,2'-bis(4-hydroxy-3-methylphenyl)propane, and one or more of these can be used in combination.

[0087] In particular, it is preferable that the polycarbonate resin mainly consists of a bisphenol-type polycarbonate resin having a skeleton derived from bisphenol. By using such a bisphenol-type polycarbonate resin, the base layer 22 exhibits even greater strength.

[0088] Furthermore, the glass transition temperature (Tg) of the polycarbonate resin contained as the main material in the base layer 22 is preferably 100°C to 190°C, and more preferably 105°C to 155°C. This makes it relatively easy to bend the resin sheet 100 into a curved shape. In addition, the durability and reliability of the resin sheet 100 can be improved.

[0089] Furthermore, the base material layer 22 may be colorless, red, blue, yellow, or any other color, as long as it is light-transmitting.

[0090] Furthermore, it is preferable that the base layer 22 also contains an ultraviolet absorber. This improves the weather resistance of the resin sheet 100.

[0091] As for the ultraviolet absorber, the same type as described above for the ultraviolet absorber included in the surface layer 21 can be used, and one or more of these can be used in combination.

[0092] Furthermore, the base layer 22 may, if necessary, contain various additives in addition to the polycarbonate resin, ultraviolet absorber, dye or pigment mentioned above, such as antioxidants, fillers, plasticizers, light stabilizers, heat absorbers, and flame retardants.

[0093] In this case, the content of polycarbonate resin in the base layer 22 is not particularly limited, but is preferably 75% by weight or more, and more preferably 85% by weight or more. By setting the content of polycarbonate resin within the above range, the resin sheet 100 can be made to exhibit excellent strength.

[0094] Furthermore, the refractive index of the substrate layer 22 at a wavelength of 589 nm is preferably between 1.3 and 1.8, and more preferably between 1.4 and 1.65. By setting the refractive index of the substrate layer 22 within the above numerical range, good optical properties can be obtained.

[0095] The thickness (T2) of the base layer 22 is preferably set to 0.1 mm or more and 1.5 mm or less, more preferably to 0.2 mm or more and 0.8 mm or less. By setting the thickness (T2) of the base layer 22 within this range, it is possible to thin the resin sheet 100 while effectively suppressing bending.

[0096] [Application] The resin sheet 100 of this embodiment is suitably used as a transparent sheet (transparent substrate) that covers the surface (front side) of a functional optical sheet (functional substrate). Specifically, it can be used as a lens for eyewear, a cover member provided to cover the window portion of a housing for a head-up display, a cover material for the front side of a functional optical sheet (functional substrate) in a windshield or the like for a vehicle, a headlamp, a curve mirror or traffic light on a road, a dome cover for a security camera, and the like.

[0097] The embodiments of the present invention have been described above with reference to the drawings, but these are merely examples of the present invention, and various other configurations can also be adopted. In the above embodiment, an example was given in which the perforated plate 30 has one hole 31, but the number, arrangement, size, etc. of the holes 31 are not limited to this. [Examples]

[0098] Next, the present invention will be described in detail with reference to examples, but the content of the present invention is not limited to these examples. (1) Preparation of the base layer Using the following raw material 1, a first resin material consisting of 98.0 parts by weight of polycarbonate resin 1 and 2.0 parts by weight of ultraviolet absorber 1 was kneaded, and the resulting mixture was extruded to produce a substrate layer (transparent substrate) with a thickness of 0.4 mm. (raw material 1) • Polycarbonate resin 1: Bisphenol A type polycarbonate (manufactured by Mitsubishi Engineering Plastics Co., Ltd., "E2000FN") • UV absorber 1: Hydroxyphenyltriazine-based UV absorber (BASF Japan, "Tinuvin 1577 ED")

[0099] (2) Preparation of UV-curable resin composition Using the following raw materials 2, UV-curable resin compositions a to c constituting the surface layer were prepared by blending and kneading them to achieve the compositions shown in Table 1. (raw material 2) • Acrylic monomer 1: A glycerin triacrylic monomer (manufactured by Toagosei Co., Ltd., "Aronics M-930") that has a branched glycol chain (aliphatic chain with 3 carbon atoms) as its main chain and three acryloyl groups as polymerizable groups. • Acrylic monomer 2: A difunctional acrylic monomer (manufactured by Shin-Nakamura Chemical Industry Co., Ltd., "A-BPE-4") comprising a straight chain with an ester bond as the main chain and two acryloyl groups as polymerizable groups. • Acrylic monomer 3: A difunctional acrylic monomer (manufactured by Shin-Nakamura Chemical Industry Co., Ltd., "A-HD-N") that has a straight glycol chain (aliphatic chain with 6 carbon atoms) as its main chain and two acryloyl groups as polymerizable groups. • Acrylic monomer 4: A polyfunctional acrylic monomer (manufactured by Shin-Etsu Chemical Co., Ltd., "KY-1211") comprising a branched chain having a repeating siloxane bond (-Si-O-Si-) as the main chain, a fluorinated hydrocarbon group as a side chain, and two or more acryloyl groups as polymerizable groups. • Acrylic oligomer 5:2 functional urethane acrylate (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., "GX-8644D") • Urethane acrylate 1: A bifunctional urethane acrylate whose main chain contains an aromatic structure (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., "GX-8644D") • Polymerization initiator 1: A photoradical polymerization initiator ("Omnirad 819" manufactured by IGMresins B.V.) that has a maximum absorption peak around 370 nm in its light absorption spectrum. • UV absorber 1: Hydroxyphenylbenzotriazole-based UV absorber (manufactured by Otsuka Chemical Co., Ltd., "RUVA-93", containing a (meth)acryloyl group as a radical polymerizable group. Maximum absorption peak: wavelength 330nm)

[0100] [Table 1]

[0101] (3) Formation of optical sheet <Example 1> (i) Preparation of a flat sheet: The UV-curable resin composition a prepared in (2) above was coated onto one surface of the 0.4 mm thick substrate layer (transparent substrate) prepared in (1) above. Subsequently, a mold (moth-eye transfer mold) was pressed onto the coated film to transfer the uneven shape, while 405 nm ultraviolet light at 1500 mJ / cm² was applied. 2 By irradiating under these conditions, the UV-curable resin composition a was cured to obtain a flat sheet having a surface nanostructure, in which a surface layer (12 μm thick) was laminated on a substrate layer. Furthermore, a glassy carbon layer with fine recesses on its surface was used for the mold (moth-eye transfer mold). The nanostructure of the resulting surface layer had an average pitch of 150 nm between the protrusions. (ii) Curving process: Next, a curving process was performed using a perforated plate. Specifically, the obtained flat sheet was cut to a size of 25 mm x 25 mm and heated at 175°C for 8 minutes. Then, the nanostructure side of the flat sheet and the perforated plate were placed facing each other and superimposed. Next, using a hemispherical pressing tool with a tip diameter of 115 mm, the flat sheet was pressed from the substrate layer side toward the hole (opening diameter 100 mm) of the perforated plate, and a protrusion was formed by pressing until the spherical tip of the pressing tool base touched the edge of the hole. Care was taken to prevent the sheet from cooling down between heating and pressing. This resulted in obtaining a resin sheet having a curved portion with a nanostructure on its convex surface.

[0102] <Example 2> A resin sheet having a curved portion with a nanostructure on its convex surface was obtained in the same manner as in Example 1, except that a hemispherical pressing tool with a tip diameter of 60 mm was used and a perforated plate with an opening diameter of 50 mm was used.

[0103] <Example 3> A resin sheet having a curved portion with a nanostructure on the convex surface was obtained in the same manner as in Example 1, except that UV-curable resin composition a was replaced with UV-curable resin composition b shown in Table 1.

[0104] <Example 4> A resin sheet having a curved portion with a nanostructure on the convex surface was obtained in the same manner as in Example 2, except that UV-curable resin composition a was replaced with UV-curable resin composition b shown in Table 1.

[0105] <Example 5> A resin sheet having a curved portion with a nanostructure on its convex surface was obtained in the same manner as in Example 3, except that a hemispherical pressing tool with a tip diameter of 12.5 mm was used and a perforated plate with an opening diameter of 10 mm was used.

[0106] <Example 6> (i) Preparation of flat sheets: A moth-eye structure film "g.moth" (registered trademark) (manufactured by Geomatec, product number 5121) was used as the surface layer, and a 0.3 mm polycarbonate sheet was used as the base layer. The two were then bonded together to produce a flat sheet. Subsequently, (ii) bending was performed in the same manner as in Example 1 to obtain a resin sheet having a curved portion with a nanostructure on the convex surface.

[0107] <Comparative Example 1> (i) Preparation of flat sheets: Flat sheets were prepared in the same manner as in Example 1. (ii) Curving process: Next, the material was curved using a press molding machine. Specifically, a convex mold (top) with a lens shape of 63.8 mmR and a concave mold (bottom) with a lens shape of 64 mmR were prepared, and the temperature of the convex mold (top) was set to 140°C and the concave mold (bottom) to 145°C. The flat sheet was placed on top of the concave mold with the nanostructure side facing downwards, and after 10 seconds, the convex mold (top) was pressed down with a press pressure of 600 N at a speed of 5 mm / s until it could be pushed down as far as possible. At that time, air was sucked from the concave mold at 0.08 MPa and the flat sheet was pressed against the concave mold and held for 60 seconds. After that, the convex mold was raised to obtain a resin sheet with a curved section.

[0108] <Comparative Example 2> A resin sheet having a curved portion was obtained in the same manner as in Comparative Example 1, except that UV-curable resin composition a was replaced with UV-curable resin composition b shown in Table 1.

[0109] 4. Evaluation and Measurement The following measurements and evaluations were performed using the obtained resin sheets. The results are shown in Table 2.

[0110] (contact angle) The contact angle was determined using a contact angle meter (Azumi Giken Co., Ltd., B100W) by the θ / 2 method, by dropping 2 μL of pure water onto the measurement site and measuring the water contact angle after 1 second. The contact angle at the vertex of the convex surface was defined as contact angle a, and contact angle b was defined as the average contact angle at two points on a straight line passing through the vertex of the convex surface, where the radius of curvature is X (mm), and the distance from the vertex is X (mm) / 5 (mm).

[0111] (curvature radius) Helling 3-D Anti-Glare Spray was applied, and the 3D shape was measured using a Keyence VR-5000 to determine the radius of curvature.

[0112] (Light transmittance) The light transmittance at a wavelength of 550 nm was measured using a spectrophotometer (JASCO Corporation, model "V-670").

[0113] (Bendability) The curved resin sheets were visually inspected, and their curvature properties were evaluated according to the following criteria. ·standard ◎: No cracks or wrinkles whatsoever. ○: There were cracks or wrinkles at the edges, but it does not affect its practical use. ×: Cracks or wrinkles present, impairing usability.

[0114] (Visibility) Curved resin sheets were observed and evaluated according to the following criteria. ·standard ◎: No clouding or smudging whatsoever. ○: There was some clouding or blurring at the edges, but it does not affect practical use. ×: Cloudy or smudged, impairing practical usability.

[0115] (weather resistance) The surface layer of a curved resin sheet was irradiated with ultraviolet light for 600 hours using a xenon weathermeter in accordance with Table 3-A method - cycle No. 3 of JIS K 7350-2. After that, the YI value of the resin sheet was measured and evaluated according to the following criteria. ·standard ◎: The change in YI as defined in JIS K 7350 is less than 3.0. ○: The change in YI as defined in JIS K 7350 is 3.0 or greater and less than 5.0. ×: The change in YI as defined in JIS K 7350 is 5.0 or greater.

[0116] [Table 2] [Explanation of symbols]

[0117] 10 nanostructures 11 Curved section 21 Surface layer 22 Base material layer 30 perforated plates 31 Hole 40 Push-in tools 100 optical sheets 110 Flat Sheet

Claims

1. A method for manufacturing a resin sheet having a curved portion with a nanostructure on its convex surface, A step of stacking a flat sheet having a nanostructure on one of its surfaces with the nanostructure side facing a perforated plate, The steps include pressing the flat sheet into the holes of the perforated plate to form the convex surface, A method for manufacturing a resin sheet having the following characteristics.

2. A method for manufacturing a resin sheet according to claim 1, Before the step of forming the convex surface, A method for manufacturing a resin sheet, comprising the step of heating the flat sheet.

3. A method for manufacturing a resin sheet according to claim 2, The step of heating the flat sheet is to heat it to 150 to 180°C, in a method for manufacturing a resin sheet.

4. A method for manufacturing a resin sheet according to claim 1 or 2, The step of forming the convex surface is a method for manufacturing a resin sheet, in which the flat sheet is pressed into each hole of the perforated plate.

5. A method for manufacturing a resin sheet according to claim 1 or 2, A method for manufacturing a resin sheet, further comprising the step of cutting the flat sheet to obtain a resin sheet after the step of forming the convex surface.

6. A method for manufacturing a resin sheet according to claim 1 or 2, A method for manufacturing a resin sheet, wherein the flat sheet is in the form of a single leaf or a continuous roll.

7. A method for manufacturing a resin sheet according to claim 1 or 2, A method for manufacturing a resin sheet, wherein the radius of curvature of the convex surface is 10 to 500 mm.

8. A method for manufacturing a resin sheet according to claim 1 or 2, The resin sheet is a resin sheet containing polycarbonate, and the method for manufacturing a resin sheet.

9. A method for manufacturing a resin sheet according to claim 1 or 2, A method for manufacturing a resin sheet, wherein the nanostructure is a fine uneven structure with an average pitch of 20 nm to 1000 nm.

10. A method for manufacturing a resin sheet according to claim 1 or 2, A method for manufacturing a resin sheet, wherein the thickness of the resin sheet is 0.1 to 0.8 mm.

11. A method for manufacturing a resin sheet according to claim 1 or 2, The resin sheet in question is used in optical components, and the method for manufacturing a resin sheet.

Citation Information

Patent Citations

  • Curved reflective polarizer film and methods of shaping

    JP2023171753A